Self-compassion and Shame Among Rape Survivors - Bhuptani, Prachi H. (Journal of interpersonal violence, 2022)
Women are at increased risk for post-traumatic stress disorder (PTSD) and depression associated with rape, and shame plays a vital role in the development and maintenance of PTSD and depression. Thus, there is a need to identify factors that may decrease shame among female survivors of adult rape. Self-compassion may be one such factor. The present study used path analysis in MPlus version 7.3 to examine the indirect effect of self-compassion on PTSD and depression via rape-related shame. We hypothesized that higher levels of self-compassion would be associated with lower levels of rape-related shame, which in turn would be associated with lower levels of PTSD and depression. College women (N = 305) who reported experiencing rape completed anonymous online surveys assessing rape, self-compassion, rape-related shame, PTSD, and depression. Consistent with our hypothesis, results indicated that self-compassion was negatively associated with assault-related shame, which in turn was positively associated with PTSD and depression. There was also a significant indirect effect of self-compassion on PTSD and depression via rape-related shame. Further, rape-related shame fully explained the relation between self-compassion and PTSD. Findings suggest that self-compassion may be an appropriate target to reduce rape-related shame and may subsequently facilitate reductions in PTSD and depression symptoms.